American lady, American painted lady, Vanessa virginiensis (Drury) (Insecta: Lepidoptera: Nymphalidae: Nymphalinae) - Donald W. Hall (EDIS, 2009)
EENY-449, a 6-page illustrated fact sheet by Donald W. Hall, is part of the Featured Creatures collection. It describes this attractive butterfly whose larvae (caterpillars) make nests by silking together leaves on host plants - distribution, description, life cycle and biology, and hosts. Includes references. Published by the UF Department of Entomology and Nematology, June 2009.